Effectiveness of daily chlorhexidine bathing for reducing gram-negative infections: A meta-analysis. (26th February 2019) - Patel, Aditi; Parikh, Parth; Dunn, Aaron N.; Otter, Jonathan A.; Thota, Priyaleela; Fraser, Thomas G.; Donskey, Curtis J.; Deshpande, Abhishek
Abstract: Objective: Multiple studies have demonstrated that daily chlorhexidine gluconate (CHG) bathing is associated with a significant reduction in infections caused by gram-positive pathogens. However, there are limited data on the effectiveness of daily CHG bathing on gram-negative infections. The aim of this study was to determine whether daily CHG bathing is effective in reducing the rate of gram-negative infections in adult intensive care unit (ICU) patients. Design: We searched MEDLINE and 3 other databases for original studies comparing daily bathing with and without CHG. Two investigators extracted data independently on baseline characteristics, study design, form and concentration of CHG, incidence, and outcomes related to gram-negative infections. Data were combined using a random-effects model and pooled relative risk ratios (RRs), and 95% confidence intervals (CIs) were derived. Results: In total, 15 studies (n = 34, 895 patients) met inclusion criteria. Daily CHG bathing was not significantly associated with a lower risk of gram-negative infections compared with controls (RR, 0.89; 95% CI, 0.73–1.08; P = .24). Subgroup analysis demonstrated that daily CHG bathing was not effective for reducing the risk of gram-negative infections caused by Acinetobacter, Escherichia coli, Klebsiella, Enterobacter, or Pseudomonas spp. Conclusions: The use of daily CHG bathing was not associated with a lower risk of gram-negative infections. Further, better designed trials with adequate power and with gram-negative infections as the primary end point are needed.